2002
DOI: 10.1210/endo.143.3.8675
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MAPK Cascades by GnRH: ERK and Jun N-Terminal Kinase Are Involved in Basal and GnRH-Stimulated Activity of the Glycoprotein Hormone LHβ-Subunit Promoter

Abstract: The role of ERK and Jun N-terminal kinase (JNK) in basal- and GnRH-stimulated LHbeta-promoter activity was examined in the gonadotroph cell line LbetaT-2. GnRH agonist (GnRH-A) stimulates the MAPK cascades ERK, JNK, and p38MAPK, with a peak at 7 min for ERK and at 60 min for JNK and p38MAPK. The rat glycoprotein hormone LHbeta-subunit promoter, linked to the chloramphenicol acetyl transferase (CAT) reporter gene, was used to follow its activation. Addition of GnRH-A (10 nM) to LbetaT-2 cells resulted in a 6-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(25 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…This mechanism of enhancing Egr-1 transcription and protein level is in keeping with previous reports that insulin regulates Egr-1 transcription (Harada et al, 1995;Mohn et al, 1990;Stumpo and Blackshear, 1991;Alexander-Bridges et al, 1992;Jhun et al, 1995;Sasaoka et al, 1993;Sartipy and Loskutoff, 2003;Keeton et al, 2003). Furthermore, others have shown that GnRH utilizes mitogen-activated protein kinase (MAPK) pathways to regulate expression of gonadotropin genes (Naor et al, 2000;Harris et al, 2002). Regulation of the equine LHβ (eLHβ) promoter by GnRH is mediated partly via a protein kinase C/MAPK pathway (Call and Wolfe, 1999).…”
Section: Resultssupporting
confidence: 87%
“…This mechanism of enhancing Egr-1 transcription and protein level is in keeping with previous reports that insulin regulates Egr-1 transcription (Harada et al, 1995;Mohn et al, 1990;Stumpo and Blackshear, 1991;Alexander-Bridges et al, 1992;Jhun et al, 1995;Sasaoka et al, 1993;Sartipy and Loskutoff, 2003;Keeton et al, 2003). Furthermore, others have shown that GnRH utilizes mitogen-activated protein kinase (MAPK) pathways to regulate expression of gonadotropin genes (Naor et al, 2000;Harris et al, 2002). Regulation of the equine LHβ (eLHβ) promoter by GnRH is mediated partly via a protein kinase C/MAPK pathway (Call and Wolfe, 1999).…”
Section: Resultssupporting
confidence: 87%
“…A membrane phospholipid, phosphatidyl inositol (4,5)-bis phosphate, is converted to inositol 3 phosphate and diacylglycerol. The former stimulates the release of calcium ion and the latter stimulates protein kinase C. Beside these signal pathways, it has been demonstrated that Gs, Gi and MAPK are also involved in the signal transduction of GnRH receptor [20][21][22][23][24]. It is thus of interest to determine how annexin A5 synthesis is controlled by GnRH in the gonadotrope.…”
mentioning
confidence: 99%
“…In human, the GnRH secretion may be regulated by estrogen and leptin [38]. It has been reported that MAP kinase contributes to the GnRH-induced LHb promoter activation in LbT2 cells [25,26]. In this study, we placed the luciferase reporter gene downstream of the rat FS promoter and found that the single and chronic treatment of LbT2 cells can activate the FS promoter.…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that GnRH induced the transient activation of the MAP kinase pathway in LbT2 cells [25,26]. Therefore, we examined whether or not the activation of the MAP kinase pathway was necessary for the GnRH-induced activation of the FS promoter.…”
Section: Involvement Of Map Kinase In Fs Promoter Activationmentioning
confidence: 97%
See 1 more Smart Citation